2019
DOI: 10.3390/agronomy9110728
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Induced Mutagenesis of Semi-Rolled Leaf1,2 Confers Curled Leaf Phenotype and Drought Tolerance by Influencing Protein Expression Patterns and ROS Scavenging in Rice (Oryza sativa L.)

Abstract: Rice leaf morphology is an essential agronomic trait to develop drought-tolerant genotypes for adequate and stable crop production in drought-prone areas. Here, rolled leaf mutant plants were acquired by CRISPR/Cas9-based mutagenesis of Semi-rolled leaf1,2 (SRL1 and SRL2) genes, and isobaric tags for relative and absolute quantification (iTRAQ) based proteomic analysis was performed to analyze the subsequent proteomic regulation events. Homozygous mutants exhibit decreased chlorophyll content, transpiration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 49 publications
(58 reference statements)
2
38
0
Order By: Relevance
“…These achievements can be used either to improve crop yields or to elucidate the function of genes controlling grain yield. Currently, CRISPR/Cas9-based gene editing has been widely used to improve the yield in crop plants [ 15 , 16 , 17 , 18 , 34 ]. Crop improvement through genome editing provides decent prospects to create mutants with desired traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These achievements can be used either to improve crop yields or to elucidate the function of genes controlling grain yield. Currently, CRISPR/Cas9-based gene editing has been widely used to improve the yield in crop plants [ 15 , 16 , 17 , 18 , 34 ]. Crop improvement through genome editing provides decent prospects to create mutants with desired traits.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the new genes responsible for the regulation of cellular growth and division and promoting grain size is worthwhile in rice breeding. Previous studies proved that the desirable mutations in yield-associated loci under natural conditions are favorable [ 3 , 4 , 5 , 6 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculation experiments proved that the mutants were highly resistant to M. oryzae, thus can be useful for future breeding programs. The mutant lines were obtained without any off-target mutations, the previously reported work also suggests that the Cas9 rarely tempts off-target mutations in rice [54,55]. The transgene-free plants were screened in a frequency ranging between 18-34% in different homozygous, heterozygous, and biallelic lines with stable transmission of mutations (Supplementary file 1, Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Some progress has been achieved by utilizing transgenic approaches to boost drought tolerance in crops [ 3 , 7 , 11 ]. Many lab studies and field trials have shown that the transgenic expression of stress-perceptive genes resulted in enhanced abiotic stress tolerance [ 12 , 13 ]. The transgenic approaches are recently the mainstream method to bioengineer drought tolerance in crop plants.…”
Section: Introductionmentioning
confidence: 99%